Germline Genetic Susceptibility Testing Among Emirati Nationals at Risk for Hereditary Breast and Ovarian Cancer Syndrome - Rifaat R. Rawashdeh; Holly Pederson; Rafal Iskanderian; Fawad Khan; Basel Altrabulsi; Stephanie Ricci; Charis Eng; Bassel Jallad; Asma Ibrahim Al Mannaei; Mohamed Salem Alameri; Azza Attia; Stephen R. Grobmyer (JCO Global Oncology)
PURPOSEBreast cancer among Emirati patients is characterized by early-onset disease and later stages at presentation. Little is known about the germline genetic variants that may contribute to these observations. The goal of this study is to characterize the rate and implications of germline genetic variants among a cohort of Emirati patients at risk for hereditary breast and ovarian cancer syndrome.MATERIALS AND METHODSA retrospective study was performed to analyze the results of clinical germline genetic testing (March 2020-January 2023) among a cohort of consecutive Emirati patients at risk for hereditary breast and ovarian cancer syndrome: group A: patients with personal history of breast or ovarian cancer (n = 135); group B: unaffected patients with family history of breast or ovarian cancer (n = 37); and group C: patients presenting for cascade testing (n = 20). Management of patients identified to have pathogenic/likely pathogenic (P/LP) variants was analyzed.RESULTSThe rate of P/LP germline variants for each group was: group A: 17.3%, group B: 16.6%, group C: 57.9%. BRCA1 gene was the most commonly identified gene harboring P/LP variants, followed by BRCA2, among this cohort. Four unrelated patients had a recurrent BRCA1 pathogenic variant: c.4065_4068del (p.Asn1355Lysfs*10). Only two patients in this series elected risk-reducing mastectomy and four patients elected risk-reducing bilateral salpingo-oophorectomy.CONCLUSIONA higher rate of P/LP variants is seen among Emirati patients at risk for hereditary breast and ovarian cancer syndrome compared with reports of similar patients from Western populations. Efforts to increase utilization and awareness of germline genetic testing are warranted among Emirati patients.